APPLICATION OF BLOW-WAVE THERAPY IN THE REHABILITATION OF PATIENTS COMPLICATED BY THE VERTEBRAL ARTERY IN CERVICAL RADICULOPATHY - Рамазанов Ш.Ф.,; Высогорцева О.Н, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. Cervical radiculopathy is a common degenerative condition of the cervical spine that leads to persistent pain, functional limitations, and a decrease in quality of life, often  complicated  by  vertebral  artery  involvement.  The  use  of  modern physiotherapeutic technologies, including shock wave therapy (SWT), is considered a promising direction in rehabilitation programs. The aim of this study was to evaluate the effectiveness of shock wave therapy in the rehabilitation of patients with cervical radiculopathy complicated by vertebral artery syndrome.